ЛИНГВОКУЛЬТУРОЛОГИЧЕСКИЕ ОСОБЕННОСТИ КОНЦЕПТА «РОДИНА/MOTHERLAND» (на материале произведений русских и английских поэтов) - Рзаева, Р.К. (SCIENCE and SOCIETY, 2020)
The article deals with the comparative-contrastive investigation of the concept «Родина/Motherland» in the literary works of the famous Russian and English poets. The analysis of the concept «Родина/Motherland» shows that there are similar and distinguishing features in the expression of this concept in Russian and English. The distinguishing peculiarities in verbal expression of the concept under study in the languages belonging to different systems can be explained by differences in the national cultures of the people.
Keywords: language and culture; Cognitive Linguistics; concept; linguoculturology; comparative-contrastive investigation; national peculiarities; culture; ethnos; similarities and differences; traditions and customs